PENGARUH MODEL PEMBELAJARAN DAN GAYA KOGNITIF TERHADAP KEMAMPUAN MENULIS TEKS PUISI (Studi Eksperimen pada Siswa Kelas X SMA Negeri 2 Lahat) - Yulia Nova; Johanes Sapri (DIADIK, 2020)
Theresearchaimstodescribethedifferencesintheabilitytowritepoetry texts  between  students  whostudywith  freeinquirylearningmodels  and  guided inquiry,betweenstudentswhohave independentfieldcognitivefieldswithdependent fields,  describe  theeffect  ofinteractions  betweenlearningmodels  and  cognitive stylesontheabilitytowritepoetry text,differencesintheabilitytowritepoetry texts betweenstudentswho haveindependentfieldcognitivestyleswhostudy withfree inquiry modelswithguidedinquiry,andsodostudentswhohavefielddependent cognitivestyles.Thisstudy useda2x2factorialdesignexperimentalmethod.The studypopulation  was  all  students  of  class  X  MIPA  SMA  Negeri  2  Lahat.  The experimentalsampleconsistedoftwoclasses,namely classXMIPA4asan experimentalclassandX MIPA 1asa controlclass, eachof whichamounted to36 students.Datacollectioninstrumentsare performance testsandGEFTtests. Hypothesistestingusestwo-wayanalysisofvariance(Anava).Theresultsshowed that(1)Theability towritepoetry textofstudentswithafreeinquiry learningmodel isnodifferentfromguidedinquiry.(2)Theability towritepoetrytextinindependent fieldcognitivestyleishigherthanfielddependent.(3)There isaninteractioneffect betweenthelearning modelandcognitivestyle ontheabilitytowritepoetrytexts.(4) Theabilitytowritepoetrytextin thefieldofindependentcognitivestylestudentsand givenafreeinquirymodelishigherthanguidedinquiry.(5)Theabilitytowrite poetrytextsofstudentswhohaveafielddependentcognitivestyleandaregivena freeinquirylearningmodel arenot different fromguided inquiry.